What Justifies Judgments of Inauthenticity? - Ahlin, Jesper (HEC Forum, 2018)
The notion of authenticity, i.e., being “genuine,” “real,” or “true to oneself,” is sometimes held as critical to a person’s autonomy, so that inauthenticity prevents the person from making autonomous decisions or leading an autonomous life. It has been pointed out that authenticity is difficult to observe in others. Therefore, judgments of inauthenticity have been found inadequate to underpin paternalistic interventions, among other things. This article delineates what justifies judgments of inauthenticity. It is argued that for persons who wish to live according to the prevailing social and moral standards and desires that are seriously undesirable according to those standards, it is justified to judge that a desire is inauthentic to the extent that it is due to causal factors that are alien to the person and to the extent that it deviates from the person’s practical identity. The article contributes to a tradition of thinking about authenticity which is known mainly from Frankfurt and Dworkin, and bridges the gap between theoretical ideals of authenticity and real authenticity-related problems in practical biomedical settings.